Neuroprotection afforded by targeting G protein-coupled receptors in heteromers and by heteromer-selective drugs - Franco, Rafael; Navarro, Gemma (Frontiers in Pharmacology, 2023)
G protein-coupled receptors (GPCRs) are the target of hundreds of approved drugs. Although these drugs were designed to target individual receptors, it is becoming increasingly apparent that GPCRs interact with each other to form heteromers. Approved drug targets are often part of a GPCR heteromer, and therefore new drugs can be developed with heteromers in mind. This review presents several strategies to selectively target GPCRs in heteromeric contexts, namely, taking advantage of i) heteromer-mediated biased agonism/signalling, ii) discovery of drugs with higher affinity for the receptor if it is part of a heteromer (heteromer selective drugs), iii) allosteric compounds directed against the interacting transmembrane domains and, eventually, iv) antagonists that block both GPCRs in a heteromer. Heteromers provide unique allosteric sites that should help designing a new type of drug that by definition would be a heteromer selective drug. The review also provides examples of rhodopsin-like class A receptors in heteromers that could be targeted to neuroprotect and/or delay the progression of diseases such as Parkinson’s and Alzheimer’s. GPCRs in heteromers (GriH) with the potential to address dyskinesias, a common complication of dopaminergic replacement therapy in parkinsonian patients, are also described.